2018
DOI: 10.1177/0895904818807311
|View full text |Cite
|
Sign up to set email alerts
|

State Boards of Education: Lesser Known Policy Actors

Abstract: Few scholars have engaged in close examinations of state boards of education (SBOEs), their make-up, or the broader implications of their influence over time. SBOE membership, authority, and impact differ significantly across the 50 states. This article reports findings from an exploratory study of three SBOEs and their role as policy actors. Thinking about SBOEs as policy actors focuses attention not only on the power, authority, and policy-making functions of SBOEs, but also on the individuals who serve on S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…To illustrate, relatively little is known about SBOEs, how SBOE members conceive of their roles and responsibilities, how they make policy decisions, which topics dominate their agendas, or how education policy issues they work on fit into the interests or concerns of districts, schools, and average citizens. Of the SBOE-related studies Young and colleagues (2019) identified, the majority consisted of “organizational reports from the 1990s or earlier, which included reviews of SBOE data and in some cases insight into the politics, values, and concerns of a given time period” (p. 207).…”
Section: Setting the Stagementioning
confidence: 99%
See 3 more Smart Citations
“…To illustrate, relatively little is known about SBOEs, how SBOE members conceive of their roles and responsibilities, how they make policy decisions, which topics dominate their agendas, or how education policy issues they work on fit into the interests or concerns of districts, schools, and average citizens. Of the SBOE-related studies Young and colleagues (2019) identified, the majority consisted of “organizational reports from the 1990s or earlier, which included reviews of SBOE data and in some cases insight into the politics, values, and concerns of a given time period” (p. 207).…”
Section: Setting the Stagementioning
confidence: 99%
“…SBOEs emerged in the early 1800s as citizen groups organized at the state level for the purpose of engaging citizens in the administration of public education (Kysilko, 2011). How citizens become SBOE members varies from state to state (Young et al, 2019). According to McCarthy and colleagues (1993), 39 of 49 states used one of the following four models for selecting SBOE members: (a) governor appoints SBOE members, SBOE appoints or recommends chief state school officer, (b) public elects SBOE members, SBOE appoints chief state school officer, (c) governor appoints SBOE members, public independently elects chief state school officer, and (d) governor appoints SBOE members and chief state school officer.…”
Section: Setting the Stagementioning
confidence: 99%
See 2 more Smart Citations
“…Young, VanGronigen, Rodriguez, Tmimi, and McCrory (2021) question the public’s digital access to (and engagement with) one of our most powerful education policy actors: State Boards of Education (SBOE). “These education policy actors are located in a critical nexus between the public and government, providing an opportunity for citizens of the state to influence the direction and governance of public schools (Young et al, 2019). ” Young et al leaned on the criteria of the Open Government Maturity Model (OGMM) to critically examine 47 SBOE websites (“electronic public faces”) against the veracity of the assumption that e-government platforms (e.g., email, listservs, social media, online chat, and discussion boards) provide citizens with opportunities to engage their SBOE.…”
mentioning
confidence: 99%